Managing online instructor workload : strategies for finding balance and success - Conceicao, Simone C. O., 1963-; Lehman, Rosemary M., 1932- (San Francisco, CA : Jossey-Bass, 2011)
'A large number of institutions are now providing online programs, requiring instructors to change the way they think about teaching and master a distinct set of workload management skills. The first book to discuss workload management for online instructors, Managing Online Instructor Workload offers practical strategies, advice, and examples for how to prioritize, balance, and manage an online teaching workload. Based on surveys and interviews, the timely and comprehensive insight in this book is essential for online instructors, instructional designers, faculty developers and others involved in online learning'-- Provided by publisher.
Issues and challenges when teaching online -- Instructors' stories for balancing workload -- Looking at workload from a design perspective -- Managing tasks and prioritizing time -- Using workload strategies for maintaining quality of life -- Final thoughts and practical implications for balancing workload.
Includes bibliographical references (p. 105-107) and index.
Keywords: Distance education -- Computer-assisted instruction; Teachers -- Workload